2013
DOI: 10.1007/s00125-013-3004-z
|View full text |Cite
|
Sign up to set email alerts
|

Implanted islets in the anterior chamber of the eye are prone to autoimmune attack in a mouse model of diabetes

Abstract: Aims/hypothesis Type 1 diabetes is an autoimmune disease resulting from the destruction of insulin-producing beta cells. Along with advances in generating replacement beta cells for treating diabetes, there is also increasing demand for non-invasive tools to evaluate the recurrence of autoimmune attack on transplanted tissue. Here, we examined the anterior chamber of the eye as a potential islet transplant site, and also evaluated whether in vivo imaging of the islets transplanted in the eye could enable real-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
58
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
3
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(61 citation statements)
references
References 30 publications
1
58
0
2
Order By: Relevance
“…Intra-vital islet imaging has been used to demonstrate the distinct morphology of the islet vasculature and analyze blood flow rate within the islets 13 . Using a transplant model in the anterior chamber of the eye, toxin-induced β-cell death 14 , the dynamics of T cell mediated graft rejection 15 , and autoimmune attack of islet transplants 16 have been analyzed. A virally induced diabetes model was used to examine the autoimmune response within the pancreas through analysis of CD8 T cell motility and interactions with β-cells 17 .…”
Section: Introductionmentioning
confidence: 99%
“…Intra-vital islet imaging has been used to demonstrate the distinct morphology of the islet vasculature and analyze blood flow rate within the islets 13 . Using a transplant model in the anterior chamber of the eye, toxin-induced β-cell death 14 , the dynamics of T cell mediated graft rejection 15 , and autoimmune attack of islet transplants 16 have been analyzed. A virally induced diabetes model was used to examine the autoimmune response within the pancreas through analysis of CD8 T cell motility and interactions with β-cells 17 .…”
Section: Introductionmentioning
confidence: 99%
“…While previous publications have indicated a risk of autoimmune attacks for islets implanted in the AC of the eye, 36 a Hematoxylin with a light Eosin stain demonstrates the absence of proinflammatory neutrophil or eosinophil (plurilobed), or lymphocytes (dark nucleus, low nuclear/cytoplasmic ratio and blue cytoplasm) infiltration ( (Fig. 3F).…”
Section: Visualization Of Fluorescent Reporters During the Developmenmentioning
confidence: 78%
“…We would define it by the following three criteria: 1) sites with an abundant, oxygen-and nutrient-rich blood flow, 2) sites that are privileged immunologically to minimize transplant graft loss, and 3) sites where transplantation can be performed with minimum invasiveness. To date, many organs have been assessed including the liver [21][22][23], renal subcapsular space [21,22], omental pouch [24,25], mesentery [26], gastrointestinal tract [27], skeletal muscle [28], subcutaneous tissue [28], eye [29], brain [30], testis [31,32], bone marrow [33], thymus [34], and spleen [35]. However, it has been difficult to find a site that meets all three criteria (Table 1).…”
Section: Candidate Transplantation Sites For Isletsmentioning
confidence: 99%
“…Hedger further revealed that rodent testes contain significant numbers of immunoregulatory cells, including Tregs [66]. And recently, Farooq showed that Tregs contribute to immune tolerance in the rodent anterior chamber when challenged by myelin antigen [29,30,32,34], little has been done in a human clinical setting. In particular, the brain or eye is problematic site for transplantation, as it would be difficult to remove a graft without damage in case of graft failure.…”
Section: Candidate Transplantation Sites For Isletsmentioning
confidence: 99%